Joint noise detection and median filtering for highly corrupted images - Koh, Jerry Min Yee. (2008)
Images are often corrupted by noise which might inevitably degrade the performance of follow-up image processing tasks. Therefore, noise detection applied before filtering is especially effective. The goal is to extend noise adaptive soft-switching median for denoising corrupted color images.